Analysis of «criminal offenses» Institute in criminal law theory (Journal of actual problems of jurisprudence, 2018)
The article deals with the analysis of the concept of «criminal offense», provides a comparative analysis of administrative offenses. The authors conducted an analysis of the world practice the institute of criminal misconduct, clarified the features of a criminal offense.Key words: criminal offense, criminal offense, Administrative Offences, the theory of criminal law, international experience, analysis of the criminal offenses.